Comparison of E-Learning and Conventional Teaching in Lecturer Teaching Technique: Students' Perspective - Akmal Bagus Jauhar; Hertiki Hertiki (LPPM Universitas PGRI Adi Buana Surabaya, 2024)
The purpose of this study is to investigate the similarities and differences between lecturers' conventional (offline) and E-learning (online) teaching techniques. The research aims to uncover insights that contribute to the development of the language teaching and learning process. The objectives included examining the delivery of course content, assessment and evaluation, student perspectives, efficiency, flexibility, engagement, and distraction in both settings. This research utilized qualitative methods with a narrative approach. Data was collected through interviews with four students from the English Department at PGRI Adi Buana University Surabaya. The findings show that face-to-face and online learning have their own unique advantages. The students consider that the delivery of the subject matter and the assessment method are the same. However, the students stated that they prefer offline learning because of the direct interaction, discussion, and supportive environment. Online learning is recognized for its practicality, flexibility and energy efficiency, although challenges such as technical issues and disruptive behavior remain. Research shows that a balanced approach, which integrates offline and online methods, can create an optimal and inclusive learning environment. For students, active participation in both environments, using technology, and providing feedback to teachers is encouraged. Lecturers are encouraged to integrate teaching methods, utilize technology for engagement, and address distractions to create a conducive online environment. Future research should explore hybrid learning models, focus on specific technological tools, and conduct longitudinal studies to understand the sustained effects of blended learning approaches.